Early Maternal and Social Deprivation Expands Neural Stem Cell Population Size and Reduces Hippocampus/Amygdala-Dependent Fear Memory - Kenny, Daun; Takahiro, Fuchigami; Natsu, Koyama; Noriko, Murata; Kazuhiro, Ikenaka; Seiji, Hitoshi (Frontiers Media S.A., 2020)
Early life stress can exert detrimental or beneficial effects on neural development and postnatal behavior depending on the timing, duration, strength, and ability to control the stressors. In this study, we utilized a maternal and social deprivation (MSD) model to investigate the effects of early life stress on neural stem cells (NSCs) and neurogenesis in the adult brain. We found that MSD during the stress-hyporesponsive period (SHRP) (early-MSD), when corticosterone secretion is suppressed, increased the size of the NSC population, whereas the same stress beyond the SHRP abrogated these effects. Early-MSD enhanced neurogenesis not only in the dentate gyrus of the hippocampus, one of the classic neurogenic regions, but also in the amygdala. In addition, mice exposed to early-MSD exhibited a reduction in amygdala/hippocampus-dependent fear memory. These results suggest that animals exposed to early life stress during the SHRP have reinforced stress resilience to cope with perceived stressors to maintain a normal homeostatic state.